Growth and Etch Rate Study of Low Temperature Anodic Silicon Dioxide Thin Films - Akarapu Ashok; Prem Pal (The Scientific World Journal)
Silicon dioxide (SiO2) thin films are most commonly used insulating films in the fabrication of silicon-based integrated circuits (ICs) and microelectromechanical systems (MEMS). Several techniques with different processing environments have been investigated to deposit silicon dioxide films at temperatures down to room temperature. Anodic oxidation of silicon is one of the low temperature processes to grow oxide films even below room temperature. In the present work, uniform silicon dioxide thin films are grown at room temperature by using anodic oxidation technique. Oxide films are synthesized in potentiostatic and potentiodynamic regimes at large applied voltages in order to investigate the effect of voltage, mechanical stirring of electrolyte, current density and the water percentage on growth rate, and the different properties of as-grown oxide films. Ellipsometry, FTIR, and SEM are employed to investigate various properties of the oxide films. A 5.25 Å/V growth rate is achieved in potentiostatic mode. In the case of potentiodynamic mode, 160 nm thickness is attained at 300 V. The oxide films developed in both modes are slightly silicon rich, uniform, and less porous. The present study is intended to inspect various properties which are considered for applications in MEMS and Microelectronics.